HUMORAL IMMUNITY AND MARKERS OF INFLAMMATION IN THE PROGNOSIS OF COMPLICATIONS OF HYPERTENSION - Navruzova Shakar Istamovna (Scholar Express Journals, 2022)
The author conducted a study of humoral immunity and markers of inflammation in patients with hypertension, studied the diagnostic value of immunological parameters for the development of methods of early prevention of patients with hypertension
Keywords: Immunity; Arterial Hypertension; Prognosis; Metabolic Syndrome